Alterations in the Coagulation and Fibrinolysis System in Pregnancy Labour and Puerperium, with Special Reference to a Possible Transitory State of Intravascular Coagulation during Labour - Gilabert, J; Aznar, J; Parrilla, J J; Regañon, E; Vila, V; Estelles, A (Thrombosis and Haemostasis, 1978)
Various tests of hemostasis were carried out during pregnancy, labour and the puerperium in a group of 259 women. Determinations were carried out in the 1st, 2nd and 3rd trimesters, in the period of dilatation, the expulsion period, the period of expulsion of the placenta and the immediate postpartum period of labour and on each of the first 5 days of the puerperium. It was confirmed that during pregnancy there is an elevation of the fibrinogen degradation producs (FDP) levels with a proportional increase in the numbers of positive protamine sulfate and ethanol tests. The proportion of positive protamine sulfate and ethanol tests reaches a maximum in the expulsion of the placenta coinciding with the presence of soluble complexes heavier than fibrinogen as detected by polyacrylamide gel electrophoresis and by column chromatography.All this indicates that there is a transitory intravascular coagulation produced during labour reaching its maximum at the time of birth and tending to become normalized in the first few days of the puerperium.